Dapagliflozin treatment for type 2 diabetes: a systematic review and meta‐analysis of randomized controlled trials. Issue 3 (March 2014) - Zhang, Mei; Zhang, Lin; Wu, Bin; Song, Haolan; An, Zhenmei; Li, Shuangqing
Abstract Context Type 2 diabetes has reached epidemic proportions and places a heavy burden on society. Dapagliflozin is a novel treatment choice for type 2 diabetes. Objective A meta‐analysis of randomized controlled trials (RCTs) was conducted to assess the efficacy and safety of dapagliflozin treatment. Data Sources Medline (via PubMed), Embase (via OVID) and the Cochrane Library (up to August 2012) were searched, and RCTs were collected. Study Selection Studies included type 2 diabetic subjects, who had been treated with dapagliflozin, and recorded HbA1c as outcomes. Data Extraction Two reviewers independently assessed articles and study quality. Patient characteristics, interventions and outcomes were collected. Data Synthesis Ten RCTs were included. Risk of bias for outcomes was low. Fixed or random effects models were used to pool the results. Dapagliflozin treatment was associated with a reduction in HbA1c [weighted mean difference (WMD): –0.53%; 95% confidence interval (CI): −0.58% to −0.47%; p < 0.00001], fasting plasma glucose (WMD: −1.06 mmol/L; 95% CI: −1.20, −0.92; p < 0.00001), and body weight (WMD: −1.63 kg; 95% CI: −1.83, −1.43; p < 0.00001). Dapagliflozin monotherapy did not lead to hypoglycaemia [relative risk (RR): 1.44; 95% CI: 0. 86, 2.41; p = 0.17], although hypoglycaemic risk increased (RR: 1.16; 95% CI: 1.05, 1.29; p = 0.005) when dapagliflozin was combined with other hypoglycaemic drugs. Dapagliflozin increased urinary glucose excretion (WMD: 26.98; 95% CI: 21.72, 32.24; p < 0.00001) and was associated with an increased risk of urinary tract infections (RR: 1.33; 95% CI: 1.10, 1.60; p = 0.004) and genital tract infections (RR: 3.23; 95% CI: 2.50, 4.18; p = 0.00001). Conclusions Dapagliflozin appears to be an effective treatment for type 2 diabetes, although it may increase the risk of urinary tract infections and genital tract infections. Copyright © 2013 John Wiley & Sons, Ltd.